Analysis of Vat Tax Management Collected By Government Treasurer: A Case Study of Online Media Companies (PT XXX) - Willy Albertus Runtunuwu; Arifin Rosid (Green Publisher Indonesia, 2025)
Government Treasurers have an obligation to collect, deposit and report the collection of Value-Added Tax on transactions with Taxable Entrepreneurs partners, Taxable Entrepreneurs partners in this case study, namely PT XXX, has difficulty in obtaining proof of Value-Added Tax collection from government treasurers. This study aims to analyze what factors are causing PT XXX not to obtain proof of Value-Added Tax collection from government treasurer collectors and provide appropriate recommendations on how to obtain it. This study is different from previous studies that evaluated the management of Value-Added Tax credits and Article 22 Income Tax. This study is a qualitative study using case studies as a research design. Data collection was carried out by literature study and interviews using semi-structured interviews. The analysis techniques used by the author are content analysis of PT XXX's receivables data, analysis of interview data, and triangulation. The causes of PT XXX's difficulties in obtaining proof of Value-Added Tax collection were identified and grouped, then with Root Cause Analysis, the main factors causing the problem of difficulty in obtaining proof of Value-Added Tax collection from government treasurers were found. The findings of this study reveal an understanding of regulations as the main causal factor, therefore more complete and clear regulations are needed as well as the socialization of regulations from the tax authorities. Steps in tax management with planning, organizing, implementing, and controlling need to be taken to minimize the causes of problems and potential tax risks in the future.